Analisis Rasio Arus Kas PT Kereta Api Indonesia (Persero) - Desiana Rachmawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
In order to achieve targets, companies need healthy funds to improve their performance. Companies can find out the availability of funds through the company's cash flow reports. This study aims to analyze PT KAI's cash flow ratio during 2014-2019. The research is descriptive quantitative by calculating the cash flow ratios. The cash flow ratio used is the cash liquidity ratio, which includes the operational cash flow ratio (AKO), the cash to interest coverage ratio (CKP), the capital expenditure ratio (PM) and the total debt ratio (TH). After calculating the ratio, do a growth ratio analysis during 2014-2019. The data used is PT KAI's audited financial statements for the 2014-2019 period. The results of the study show that PT KAI's cash flow ratio as a whole is still in a bad condition. The four ratios of operating cash flows used in this study, there are three ratios have a value of less than 1, namely the ratio of cash sweeps to current debt (AKO), the ratio of capital expenditure (PM) and the ratio amount of debt (TH). Meanwhile, one other ratio, namely the cash to interest coverage ratio (CKB), is worth more than 1.